Features of the use of the statistical classification at the therapeutic dental reception (LLC "Endo Press", 2020)
A review is given on available literature on maintaining and keeping documents with the use of ICD-10, models and stages of its implementation are also considered in this work. It is provided a certain range of literary sources, reflecting the adaptation features of ICD, as well as an example of its practical application at the Department of Еndodontics and Сariology of MSUMD while implementing Federal State educational standards of the third generation.